The interplay of parental monitoring and socioeconomic status in predicting minor delinquency between and within adolescents. (30th June 2017) - Rekker, Roderik; Keijsers, Loes; Branje, Susan; Koot, Hans; Meeus, Wim
ABSTRACT: This six‐wave multi‐informant longitudinal study on Dutch adolescents ( N = 824; age 12–18) examined the interplay of socioeconomic status with parental monitoring in predicting minor delinquency. Fixed‐effects negative binomial regression analyses revealed that this interplay is different within adolescents across time than between adolescents. Between individuals, parental solicitation and control were not significantly associated with delinquency after controlling for SES: Adolescents whose parents exercised more monitoring did not offend less than others. Within individuals, higher levels of parental control were unexpectedly associated with more delinquency, but this relation was dependent on SES: Low‐SES adolescents, but not high‐SES adolescents, offended more during periods in which their parents exercised more control than during other periods with less control. In contrast to earlier work, this finding suggests that monitoring could be least effective when needed most. Low‐SES parents might not use monitoring effectively and become overcontrolling when their child goes astray.